Impact of Psychological Contract Violation on Turnover Intentions among Project Employee, Mediating role of Burnout and Moderating role of Self-Efficacy - Mehmood, Shehza; Rao, Shanza Naseer; Gul, Dr Rani (Journal of Business & Tourism, 2024)
Psychological Contract Violation can have devastating consequences, including Employee Turnover Intentions, which is a critical concern for organizations, leading to significant costs and potential loss of competitive advantage. This study investigated how Psychological Contract Violation influence employees' intentions to leave IT software development companies based in Rawalpindi and Islamabad. Additionally, it explores the mediating role of burnout and the moderating effect of self-efficacy. Utilizing a quantitative research methodology and Hayes Process Macros Model 7, this research examined the responses of 270 IT employees. Results disclosed a notable positive relation between Psychological Contract Violation and Employee Turnover Intentions, with Burnout identified as a mediator in this relationship. Contrary to expectations, the study found no significant moderation by self-efficacy in the relation between Psychological Contract Violation and Burnout. This study highlights the importance of addressing burnout and promoting employee well-being to mitigate turnover risks associated with psychological contract violation.